The Direction Of Education In Indonesia In The Endemic - Wismanto Hadi, Wahyu; Ragil Supriyono; Fika Wili Susanti; Hernida Dwi Lestari (International Journal of Educational Research & Social Sciences, 2022)
Pandemic Covid-19, which occurs almost all over the world and is a health crisis for mankind. In the world of education, the pandemic Covid-19 impact on the closure of schools and colleges not only in Indonesia but also in the world. Until 3 October 2021, based on a map of the spread of Covid-19 in Indonesia, cases of Covid-19 confirmed as much as 4.218.142. Various vaccines such as Sinovac, AstraZeneca, Pfizer and BioTech, as well as Moderna brought to Indonesia by the Ministry of foreign Affairs. The emergence of pandemic COVID-19 impact the process of learning to walk with the help of digital technology such as Google Classroom, Home Study, Zoom, video conference, phone or live chat, etc. The problems experienced in the world of education, especially by the students or the students, teachers, and parents in the teaching and learning activities online is the lack of mastery of the technology, the addition of cost Internet quota, increasing job for parents in assisting children in the process of teaching and learning, communication and socialization between students or students will be declined, the process of interaction of teachers and parents are becoming increasingly reduced and the working hours will be limited for teachers or lecturers and students or students because they have to communicate and coordinate each time Learning with the method of online less effective for stakeholders who are accustomed to the conventional patterns. Teachers, lecturers and students as well as students experience the transformation of digital very fast with the online make the teacher or lecturer to be less than the maximum, the implementation of online learning with the internet network is less stable, the ability to use media online learning still haven't mastered that resulted in the student or the student feel the saturation. The educational process that is already running in the pademi carried out by the method of blended learning as an appropriate solution. On the method of a mixture of learning, students can experience learning face to face in the process of practicum and online in the provision of learning materials. With this method the expected process of learning is still running in a more secure and comfortable as well as stay ahead in the effort to realize the generation of competitiveness for the betterment of the nation of Indonesia.